2019
DOI: 10.1590/2317-1545v41n1193955
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and deterioration of Inga vera ssp. affinis embryos stored at different temperatures 1

Abstract: Inga vera ssp. affinis embryos at different maturity stages and with various water contents had their CO2 production and O2 consumption analyzed, and then compared to those of Phaseolus vulgaris L. seeds. The results showed that the lower the temperature, the lower the respiratory rates and the more intense the other oxidative processes of I. vera embryos. On the other hand, the same did not happen in P. vulgaris seeds. Oxidative reactions, including respiration, reduced the germinative capacity and compromise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
5
0
7
Order By: Relevance
“…Contudo, surpreendentemente mesmo a 5°C, temperatura de câmara fria considerada favorável para a conservação desses embriões (Bilia & Barbedo 1997, Andréo et al 2006, Faria 2006, Bonjovani & Barbedo 2008, ainda houve intensa respiração. Assim como observado por Bonjovani & Barbedo (2019), mesmo em temperatura negativa (-2°C) os embriões mantiveram-se metabolicamente ativos.…”
Section: Resultsunclassified
“…Contudo, surpreendentemente mesmo a 5°C, temperatura de câmara fria considerada favorável para a conservação desses embriões (Bilia & Barbedo 1997, Andréo et al 2006, Faria 2006, Bonjovani & Barbedo 2008, ainda houve intensa respiração. Assim como observado por Bonjovani & Barbedo (2019), mesmo em temperatura negativa (-2°C) os embriões mantiveram-se metabolicamente ativos.…”
Section: Resultsunclassified
“…The results also made it evident that there is a need to remove all water from types 4 and 5 (Vertucci and Farrant, 1995) to enable tolerance to freezing. Although desiccation-sensitive seeds are often considered to be intolerant to freezing (Goldfarb et al, 2017, and references contained), those of Inga vera tolerated sub-zero temperatures, a fact also reported by Bonjovani and Barbedo (2008) for -2 °C. Seeds stored with high water contents are susceptible to damage caused by freezing temperatures, owing to the formation of ice crystals in the tissues, which leads to loss of viability (Fonseca and Freire, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…After the control sample (no drying) was removed, the embryos were subjected to two levels of intermittent drying in a forced air circulation oven, in simple layers without overlapping. The levels were alternated: ten hours at 30 ± 1 °C and fourteen hours at 22 ± 2 °C (Bonjovani and Barbedo, 2008), until their water contents were close to 53% (level 1) and 46% (level 2), which are reference values for sensitivity analysis to desiccation of embryos of Inga vera (Bonjovani and Barbedo, 2008;Lamarca and Barbedo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing different strategies of species propagation, I. vera seeds are dispersed with high content of water (hydration level), which allows storage only for a period shorter than 20 days at room temperature (Barbedo and Cicero, 2000). Caccere et al (2013) studied these seeds observed high metabolic activity from the early stages of development until the end of the maturation, and Bonjovani and Barbedo (2019) showed that oxidative processes are involved in this activity. Our results indicate an opposite strategy in E. speciosa seeds, characterized by a dramatic decline in metabolism, which could classify them as orthodox.…”
Section: Discussionmentioning
confidence: 99%